Pertumbuhan dan Produksi Beberapa Varietas Kacang Hijau (Vigna radiata L) dengan Pemberian Beberapa Dosis Pupuk NPK - Wayan Sugita (Universitas Merdeka Madiun, 2023)
Abstract - The use of several varieties of green beans supported by NPK fertilizer and relatively easy cultivation techniques means this plant has good prospects as a business opportunity in the agribusiness sector because demand is quite large yearly. This research aimed to evaluate the appropriate dose of NPK fertilizer for the growth of several Mung Bean varieties. This research used a Randomized Block Design to treat several green bean varieties, Vima 1, Vima 2 and Vima 3. At the same time, the NPK fertilizer doses were P0 (without fertilizer), P1 (100 kg/ha), P2 (150 kg/ha) and P3 (200 kg /Ha). The research showed that fertilizer application only affected plant height, number of pods per plant and seed production per ha. At the same time, several varieties affected plant height and seed production per ha. The interaction of fertilizer application and several varieties significantly affects seed production per ha. Based on research results, applying fertilizer at a dose of 200 kg/ha gave the highest results in the growth and production of green beans. Based on the results of this research, it is also known that using several green bean varieties shows that the V-3 variety provides the best results in growth, and the V-2 variety provides the best results in production.